CERIUM (IV) AMMONIUM NITRATE (CAN) AS A CATALYST IN WATER: A SIMPLE, PROFICIENT AND GREEN APPROACH FOR THE SYNTHESIS OF TETRAHYDROPYRIMIDINE QUINOLONES - Geramizadegan, Mahsa; Mahdavinia, Gholam Hossein (Journal of the Chilean Chemical Society, 2017)
We report here a facile, mild and efficient synthesis of functionalized tetrahydropyrimidine quinolones via one pot three-component condensation of aromatic aldehydes, N,N-dimethyl barbituricacid (barbituricacid), 4-hydroxy-1-methylquinolin-2(1H)-one and using a cerium ammonium nitrate (CAN) as a green catalyst in aqueous media-water (as a green ideal solvent) is described. The significant advantages of this protocol are short reaction time, simple work up procedure and reduced environmental impact, wide substrate scope; generally very good to excellent yields and starting materials are inexpensive and commercially available. The structures of these compounds were established on the basis of IR, 1H NMR, 13C NMR spectra.